Japanese encephalitis presenting as transverse myelitis: An uncommon presentation - Cornelius, Leema Pauline; Elango, Neeraj; Jeyaram, venkateswaran Kuttava (Indian Journal of Case Reports, 2022)
Japanese Encephalitis Virus (JEV) is the main cause of viral encephalitis in South East Asia. Commonly, it presents as an acute encephalitic syndrome with fever, headache, seizures, and altered sensorium as clinical manifestations. However, there can be atypical presentations such as acute transverse myelitis (ATM) as the initial manifestation. Clinicians should be aware of such possibilities and myelitis due to the JE virus should be considered as a differential in children presenting with encephalomyelitis.